DHE-Induced Peripheral Arterial Vasospasm in Primary Raynaud Phenomenon: Case Report. (April 2019) - Khalife, Jane; Lauritsen, Clinton G.; Liang, John; Shah, Syed O.
Dihydroergotamine (DHE) is primarily a serotonin 5HT1B and 5HT1D receptor agonist used for acute migraine treatment. It is associated with acute vasoconstriction mediated through the 5HT1B receptor and is contraindicated in patients with history of cardiac disease and peripheral vascular disease. We present a case of acute peripheral arterial vasospasm in a patient with primary Raynaud phenomenon while receiving inpatient treatment for status migrainosus with intravenous (IV) DHE. The patient is a 35-year-old female with a history of chronic migraine and primary Raynaud phenomenon. After 15 doses of IV DHE, the patient reported paresthesias of the right hand and was noted to have absent right radial and ulnar pulses to palpation. Portable arterial Doppler study demonstrated abnormal flat line pulse volume recordings (PVRs) in the right second, third, and fourth digits, with markedly dampened PVR in the right thumb and fifth finger along with no ulnar PVR detectable at the wrist. Duplex revealed bilateral severely diminished flow in the right ulnar and radial arteries without acute occlusions. Computed tomography angiogram of right upper extremity visualized arteries through the mid-forearm but not distally. Dihydroergotamine was discontinued, and the patient was started on oral amlodipine and aspirin. Repeat Doppler ultrasound 3 days later revealed normal arm and digital waveforms bilaterally consistent with resolution of vasospasm. This case highlights a potential complication of IV DHE therapy. Risk may be increased in patients with primary Raynaud phenomenon. We suggest cautious use of IV DHE in this population.